Answer:
9
Step-by-step explanation:
Answer:
Step-by-step explanation:
We are given that
![f(x)=6(\frac{1}{3})^x](https://tex.z-dn.net/?f=f%28x%29%3D6%28%5Cfrac%7B1%7D%7B3%7D%29%5Ex)
Function f decreases from quadrant 2 to quadrant 1 and approaches y=0
It cut the y- axis at (0,6) and passing through the point (1,2).
Function g(x) approaches y=0 in quadrant 2 and increases into quadrant 1.
It passing through the point (-1,2) and cut the y-axis at point (0,6).
Reflection across y- axis:
Rule of transformation is given by
![(x,y)\rightarrow (-x,y)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Crightarrow%20%28-x%2Cy%29)
Using the rule then we get
![g(x)=6(\frac{1}{3})^{-x}=6(3)^x](https://tex.z-dn.net/?f=g%28x%29%3D6%28%5Cfrac%7B1%7D%7B3%7D%29%5E%7B-x%7D%3D6%283%29%5Ex)
By using
![x^{-a}=\frac{1}{x^a}](https://tex.z-dn.net/?f=x%5E%7B-a%7D%3D%5Cfrac%7B1%7D%7Bx%5Ea%7D)
Substitute x=-1
![g(-1)=6\times (\frac{1}{3})=2](https://tex.z-dn.net/?f=g%28-1%29%3D6%5Ctimes%20%28%5Cfrac%7B1%7D%7B3%7D%29%3D2)
Substitute x=0
![g(0)=6](https://tex.z-dn.net/?f=g%280%29%3D6)
Therefore,
is true.
Answer:
4y-12
Step-by-step explanation:
To multiply a sum (or difference) by a factor, each summand (or minuend and subtrahend) is multiplied by this factor and the resulting products are added (or subtracted).
If the operation outside the parentheses (in this case, the multiplication) is commutative, then left-distributivity implies right-distributivity and vice versa, and one talks simply of distributivity.
Answer:
20= v+9+( -16 )
20= v-( 7 )
27= v
Step-by-step explanation:
Adding a negative is the sane as subtracting. Add like terms. Add 7 to both sides. 27= v